Management of acquired haemophilia A - Tiede, A.; Scharf, R. E.; Dobbelstein, C.; Werwitzke, S. (Hämostaseologie, 2015)
Acquired haemophilia A (AHA) is caused by autoantibody inhibitors of coagulation factor VIII (FVIII : C). Recent onset of bleeds and isolated prolongation of the activated partial thromboplastin time (aPTT) are characteristic features of the disorder. Reduced FVIII : C activity and a detectable FVIII : C inhibitor in the Bethesda assay confirm the diagnosis. Patients should be referred to expert centres, whenever possible, and invasive procedures with a high risk of bleeding must be avoided, until haemostasis has been secured by adequate therapy.Bypassing agents capable of inducing sufficient thrombin formation in the presence of FVIII : C inhibitors are treatment of choice, including currently available recombinant factor VIIa (NovoSeven™) and activated prothrombin complex concentrate (FEIBA™). These agents represent first line therapy to control acute or severe bleeds. To eradicate inhibitors, immunosuppressive treatment (IST) is indicated in patients with AHA. Glucocorticoids, cytotoxic agents and rituximab are most widely used. However, an ideal IST regimen has not been established so far. Adverse events of IST, including infections as the foremost cause death, are frequent complications in AHA.
Keywords: Factor VIII : C; inhibitor; bleeding; recombinant factor VIIa; activated prothrombin complex concentrate; immunosuppression